Theoria, praxis, and the contemplative life after Plato and Aristotle - Bénatouïl, Thomas; Bonazzi, Mauro, 1973- (Philosophia antiqua, 2012)
This volume deals with the appropriations, criticism and transformation of Plato's and Aristotle's positions about theory, practice and the contemplative life, including their epistemological and metaphysical foundations, from Theophrastus to the end of Antiquity (including Jewish and Christian authors).